2011
DOI: 10.1016/j.jep.2011.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Novel acylated steroidal glycosides from Caralluma tuberculata induce caspase-dependent apoptosis in cancer cells

Abstract: Aim of the study: Pregnane glycosides are potent cytotoxic agents which may represent new leads in the development of anti-tumour drugs, particularly in the treatment of breast cancer, because of the structural similarity to estrogenic agonists. Caralluma species are natural sources of a wide variety of pregnane glycosides. The aim of the study was to isolate, using an activity-guided fractionation approach, novel pregnane glycosides for testing on breast cancer and other tumour lines. Materials and Methods:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…In these molecules, the sugar moiety is mostly linked at the C-3 position of the aglycone and generally occurs as a linear rather than a branched oligosaccharide chain (Panda et al, 2006). In recent years, several studies have reported that pregnane glycosides have considerable bioactivity, including compounds with antiproliferative (Cioffi et al, 2006;Plaza et al, 2005), cytotoxic (Braca et al, 2002;De Leo et al, 2005;Chen et al, 2010;Waheeda et al, 2011;Al-Massarani et al, 2012), antifungal (Yoon et al, 2011) and antidepressant (Yang et al, 2011) activities.…”
Section: Introductionmentioning
confidence: 99%
“…In these molecules, the sugar moiety is mostly linked at the C-3 position of the aglycone and generally occurs as a linear rather than a branched oligosaccharide chain (Panda et al, 2006). In recent years, several studies have reported that pregnane glycosides have considerable bioactivity, including compounds with antiproliferative (Cioffi et al, 2006;Plaza et al, 2005), cytotoxic (Braca et al, 2002;De Leo et al, 2005;Chen et al, 2010;Waheeda et al, 2011;Al-Massarani et al, 2012), antifungal (Yoon et al, 2011) and antidepressant (Yang et al, 2011) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of safety profile of C. tuberculata by gross behavioural, acute and chronic toxicity study of ethyl acetate fraction of ethanol extract in Swiss albino mice support the safe folklore use of this plant as a drug as it did not affect the biochemical and hematological parameters and also has no effect on the growth of vital body organs [25]. Cytotoxicty.…”
Section: Acute and Chronic Toxicitymentioning
confidence: 73%
“…The ethyl acetate fraction of C. tuberculata was found to be the most potent antiproliferative fraction against breast cancer (Michigan Cancer Foundation‐7 (MCF7) human breast oestrogen‐dependent adenocarcinoma and MDA‐MB‐468 human breast oestrogen‐independent adenocarcinoma) and other tumour cell lines (Caco‐2 human colon adenocarcinoma). Steroid glycosides isolated from C. tuberculata were found to possess moderate, micromolar cytotoxic activity on breast cancer and other cells in vitro [10]. Certain cytotoxic steroids have already been identified in genus Caralluma (Figure ).…”
Section: Pharmacological Reportsmentioning
confidence: 97%
“…Several species of the genus Caralluma are rich in pregnane glycosides, flavone and megastigmane glycosides, and various esters, which authenticate its medicinal importance [7–9]. Antioxidant, anticancer, antidiabetic, anti‐inflamatory, antimicrobial, anti‐eczemic, antimalarial and antifungal properties of various Caralluma extracts showed its pharmacological importance [10,11]. It is also worth mentioning that C. tuberculata and C. edulis were previously cited as Boucerosia tuberculata and B. edulis in Pakistan, which were later identified as Caralluma spp [1,12]…”
Section: Introductionmentioning
confidence: 99%